2005
DOI: 10.1089/tmj.2005.11.63
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Telemonitoring: A Comment on the Literature

Abstract: Telemonitoring, is defined as the use of information technology to monitor patients at a distance. This literature review suggests that the most promising applications for telemonitoring is for chronic illnesses such as cardiopulmonary disease, asthma, and heart failure in the home. Fetal heart rate monitoring and infant cardiopulmonary functions have also been monitored at a distance, as well as coagulation, or the level of activity of elderly people, assessed by the intelligent home monitoring devices. Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
141
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(150 citation statements)
references
References 26 publications
0
141
0
9
Order By: Relevance
“…On the other hand, home telecare is a rapidly evolving domain focused on providing care in a home setting with the primary intent of supporting the patient rather than the health professionals. Home telemonitoring is used in a more restrictive sense and encompasses the use of audio, video, and other telecommunication technologies to monitor patient status at a distance [2,3].…”
Section: Key Identificationmentioning
confidence: 99%
“…On the other hand, home telecare is a rapidly evolving domain focused on providing care in a home setting with the primary intent of supporting the patient rather than the health professionals. Home telemonitoring is used in a more restrictive sense and encompasses the use of audio, video, and other telecommunication technologies to monitor patient status at a distance [2,3].…”
Section: Key Identificationmentioning
confidence: 99%
“…In this regard Meystre (2005) concluded that longterm disease monitoring at home through TM represents a promising application of telemonitoring technology for the delivery of cost effective quality healthcare. A recent review of home telemonitoring for CDs showed a good level of accuracy and reliability of transmitted data (Pare et al, 2007).…”
Section: 4mentioning
confidence: 99%
“…The interrupter set consists of a shutter (Micro Medical Ltd.) combined with flow (Lilly type pneumotachometer, resolution of 0.01 dm 3 ·s -1 , range of 0-2 dm 3 ·s -1 ) and pressure (piezoresistive) transducers. The shutter interrupts the expiratory flow producing a change of pressure, and both signals are sampled by a 12-bit A/D converter at 500 Hz.…”
Section: Hardwarementioning
confidence: 99%